Iron, Enhancer, and Inhibitor Intake in Relation to Ferritin and Hemoglobin Levels Among Adolescent Girls in Pekalongan, Central Java - Damayanti, Yuliana Kusuma; Margawati, Ani; Noer, Etika Ratna (Journal of Health and Nutrition Research, 2025)
Anemia among Indonesian adolescent girls remains a major issue, with 15.5% nationally and 49.47% in Pekalongan affected. Ferritin, a sensitive marker of iron stores, reflects early iron deficiency influenced by diet, enhanced by vitamin C, and inhibited by calcium and phytic acid. This study aimed to investigate the relationship between iron, enhancer, and inhibitor intake and ferritin and hemoglobin levels in adolescent girls. An observational study with a cross-sectional design was conducted among 80 female students in Pekalongan, Central Java. Intake of iron, protein, vitamin A, vitamin C, fiber, calcium, and phytic acid was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Hemoglobin levels were measured using a Hematology Analyzer, and ferritin was analyzed using the ELISA method. Data were analyzed using Pearson or Spearman correlation and multiple linear regression tests. The results show that ferritin levels were significantly correlated with iron (r = 0.293; p = 0.008) and vitamin C intake (r = 0.298; p = 0.007), and negatively correlated with calcium and phytic acid (r = –0.673; p < 0.001). Hemoglobin levels were correlated with protein (r=0.232; p=0.035), calcium (r=–0.240; p=0.032), and phytic acid (r=–0.241; p=0.032). Multivariate analysis revealed that ferritin levels were influenced simultaneously by iron, vitamin C, and calcium intake (CI: 95%, p < 0.001), while hemoglobin levels were influenced simultaneously by protein, fiber, and phytic acid intake (CI: 95%, p = 0.019). Iron, vitamin C, calcium, protein, fiber, and phytic acid intake influence ferritin and hemoglobin levels. Ferritin should be used as an early marker of iron deficiency, and interventions promoting higher iron and vitamin C intake while limiting inhibitors are recommended for adolescent girls.